Limit of a series

Calculus Level 3

lim n 1 2 + 3 4 + 5 6 + . . . 2 n n 2 + 1 + 4 n 2 1 \large \lim_{n \to \infty} \dfrac{1 - 2 + 3 - 4 + 5 - 6 + ... - 2n}{\sqrt{n^2 + 1} + \sqrt{4n^2 - 1}} If the value of above limit equals to a b - \dfrac{a}{b} , where a a and b b are positive co-prime integers, find the value of a b ab .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ram Mohith
Aug 23, 2018

lim n ( 1 + 3 + 5 + . . . n t e r m s ) 2 ( 1 + 2 + 3 + . . . n t e r m s ) n 2 + 1 + 4 n 2 1 \lim_{n \to \infty} \dfrac{(1 + 3 + 5 + ... n~terms) - 2(1 + 2 + 3 + ... n~terms)}{\sqrt{n^2 + 1} + \sqrt{4n^2 - 1}}

lim n n 2 n ( n + 1 ) n 2 + 1 + 4 n 2 1 \lim_{n \to \infty} \dfrac{n^2 - n(n + 1)}{\sqrt{n^2 + 1} + \sqrt{4n^2 - 1}}

lim n n n 1 + 1 n 2 + n 4 1 n 2 \lim_{n \to \infty} \dfrac{-n}{n \sqrt{1 + \dfrac{1}{n^2}} + n \sqrt{4 - \dfrac{1}{n^2}}}

lim 1 n 0 1 1 + 1 n 2 + 4 1 n 2 \lim_{\frac{1}{n} \to 0} \dfrac{-1}{\sqrt{1 + \dfrac{1}{n^2}} + \sqrt{4 - \dfrac{1}{n^2}}}

1 1 + 4 = 1 1 + 2 = 1 3 = a b \implies - \dfrac{1}{\sqrt{1} + \sqrt{4}} = - \dfrac{1}{1 + 2} = - \dfrac{1}{3} = - \dfrac{a}{b}

a × b = 3 \implies a \times b = 3

In step 1, you've rearranged the sum in the numerator when it isn't convergent in the limit. This isn't valid.

D G - 2 years, 9 months ago

Log in to reply

No it is convergent but as n tends to infinity there are infinite terms.

Ram Mohith - 2 years, 9 months ago
Chew-Seong Cheong
Aug 23, 2018

L = lim n 1 2 + 3 4 + 5 6 + 2 n n 2 + 1 + 4 n 2 1 = lim n ( 1 + 2 + 3 + + 2 n ) 4 ( 1 + 2 + 3 + + n ) n 2 + 1 + 4 n 2 1 = lim n 2 n ( 2 n + 1 ) 2 4 ( n ( n + 1 ) 2 ) n 2 + 1 + 4 n 2 1 = lim n n n 2 + 1 + 4 n 2 1 = lim n n n 1 + 1 n 2 + 2 n 1 1 4 n 2 Divide up and down by n = lim n 1 1 + 1 n 2 + 2 1 1 4 n 2 = 1 1 + 2 = 1 3 \begin{aligned} L & = \lim_{n \to \infty} \frac {1-2+3-4+5-6+\cdots -2n}{\sqrt{n^2+1}+\sqrt{4n^2-1}} \\ & = \lim_{n \to \infty} \frac {(1+2+3+\cdots + 2n) - 4(1+2+3+\cdots+n)}{\sqrt{n^2+1}+\sqrt{4n^2-1}} \\ & = \lim_{n \to \infty} \frac {\frac {2n(2n+1)}2 - 4\left(\frac {n(n+1)}2\right)}{\sqrt{n^2+1}+\sqrt{4n^2-1}} \\ & = \lim_{n \to \infty} \frac {-n}{\sqrt{n^2+1}+\sqrt{4n^2-1}} \\ & = \lim_{n \to \infty} \frac {-n}{n\sqrt{1+\frac 1{n^2}}+2n\sqrt{1-\frac 1{4n^2}}} & \small \color{#3D99F6} \text{Divide up and down by }n \\ & = \lim_{n \to \infty} \frac {-1}{\sqrt{1+\frac 1{n^2}}+2\sqrt{1-\frac 1{4n^2}}} \\ & = \frac {-1}{1+2} = - \frac 13 \end{aligned}

Therefore, a b = 1 × 3 = 3 ab = 1\times 3 = \boxed 3 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...